English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

so far i have (x-3)(x-2)(x+1). However, i do not know how to fit in the second part of the question.

2006-12-18 15:37:00 · 6 answers · asked by C 1 in Science & Mathematics Mathematics

6 answers

Put y=A(x-3)(x-2)(x+1) where A is some constant. Now substitute x=-2 and y=40 to get A=-2.
So the equation is:

y=-2(x-3)(x-2)(x+1)

2006-12-18 15:48:58 · answer #1 · answered by martina_ie 3 · 0 0

Plug in -2:

(-2-3)(-2-2)(-2+1) = (-5)(-4)(-1) = -20

You want the value of this equation to be 40 at -2. It is currently -20. Thus, you must multiply it by 40/(-20) or -2. So you have:

-2(x-3)(x-2)(x-1)

And you are done. Note that the reason we multiply by a constant instead of using some other operation to change the value of the polynomial (such as adding 60) is that any other operation would change the zeros of the polynomial.

2006-12-18 15:47:45 · answer #2 · answered by Pascal 7 · 0 0

The key to the solution for you is to realize that their are an infinite number of solutions for the first part, all being given by a non-zero constant multiple of your answer:
A(x-2)(x-3)(x+1)

So all you need is fit your function to the condition by equating the value of the function at -2 to 40.

A(-2-2)(-2-3)(-2+1) = 40 or -20A = 40

So A = -2

So the equation is -2(x-3)(x-2)(x+1)

2006-12-18 15:44:56 · answer #3 · answered by mulla sadra 3 · 1 0

First locate the slope of the line. The slope is given by using upward thrust/run. additionally commonplace as. m= (y1 - y2) / (x1 - x2) So the slope is: m = (a million - [-2] ) / (3 - [-a million]) = 3 / 4 via fact the slope is 3/4 you are able to placed it into an equation like this: y = mx + C y = (3/4)x + C Now plug in one among your factors to be certain what C is. a million = (3/4)(3) + C a million = (9/4) + C (4/4) - (9/4) = C -5/4 = C So C is comparable to -5/4. So your very final equation is: y = (3/4)x - (5/4)

2016-12-15 04:00:05 · answer #4 · answered by binford 4 · 0 0

(x - 3)(x - 2)(x + 1)

f(-2) = (-2 - 3)(-2 - 2)(-2 + 1)
f(-2) = (-5)(-4)(-1)
f(-2) = (20 * -1) = -20

40/-20 = -2

f(x) = -2(x - 3)(x - 2)(x + 1)
f(x) = -2(x^2 - 2x - 3x + 6)(x + 1)
f(x) = -2(x^2 - 5x + 6)(x + 1)
f(x) = -2(x^3 + x^2 - 5x^2 - 5x + 6x + 6)
f(x) = -2(x^3 - 4x^2 + x + 6)

ANS : f(x) = -2x^3 + 8x^2 - 2x - 12

if you plug in -2 for x, you will get it to equal 40

2006-12-18 15:51:05 · answer #5 · answered by Sherman81 6 · 0 0

y = (x-3)(x-2)(x+1)

if x = -2 then y = -5 * -4 * -1 = - 20 , but we want 40

40 / (-20) = -2

so let y = -2(x-3)(x-2)(x+1)

2006-12-18 15:44:19 · answer #6 · answered by ___ 4 · 1 0

fedest.com, questions and answers